Dyslipidemia and its Correlates among HIV Infected Children on HAART Attending Mbarara Regional Referral Hospital - Nampijja, Dorah; Kumbakumba, Elias; Bajunirwe, Francis; Kiwanuka, Julius (International clinical pathology journal, 2018)
Background—HAART and chronic HIV associated inflammation has been attributed to abnormal lipids in HIV infected people. Little is known about dyslipidemia among children in Uganda in the era of increasing Highly Active Antiretroviral Therapy (HAART) use. We determined the prevalence of lipid abnormalities, the correlation of the lipid abnormalities to CD4 count, HIV clinical stage and duration on HAART among HIV infected children. Methods—This was a cross-sectional, descriptive and analytical study of HIV infected children age 1–17 years receiving HAART for more than 6 months in Mbarara Regional Referral Hospital. Consent and assent were obtained as appropriate. Sociodemographic, clinical and immunological data were collected and recorded in a questionnaire. A blood sample was taken for lipid profiling. Dyslipidemia was defined as any low HDL (<=40mg/dl), high LDL (>130mg/dl), high TG (>130mg/dl) and a high total cholesterol (>200mg/dl) or a combination of these in the study population. The proportion of children with dyslipidemia was calculated and logistic regression analysis for associated factors. Results—The mean age was 118 months (SD 49 months) with 49.5% of the children male and 62.1% had severe HIV disease at initiation of HAART. Mean duration of HAART was 55.6 months (SD 31.2 months). The prevalence of dyslipidemia was 74%. Among the children with dyslipidemia, 56.6% exhibited low HDL, 22% had hypertriglyceridemia, 15.6% had high LDL and 11% had hypercholesterolemia. We found significant association between dyslipidemia and WHO clinical stage at initiation of HAART (AOR 2.9 1.05 – 8.45 p=0.040). Conclusion—There was a high prevalence of dyslipidemia associated with severe HIV disease at initiation of HAART among HIV-infected children on HAART
Keywords: HIV infected; Dyslipidemia; Children; HAART